A Multimodal Analysis of Public Service Announcement for Covid-19 - Firman Nur Rochman Herawan Hartaman (Passage: Journal of English Language and Literature, 2023)
This study examines the interactive meaning and level of realness in three Public Service Announcement poster for Covid-19. The data are in the form of pictures and they are obtained through accessing and downloading them from The Directorate of Health Promotion and Community Empowerment of Indonesian Ministry of Health’s Website. This study used qualitative approach since the researcher was trying to observe, interpret, and understand how an in-depth analysis of visual elements is used to make meaning out of a social phenomenon product which in this case are PSA posters. The theoretical framework used for this study is visual grammar by Kress and Van Leeuwen’s (2006) to analyze the interactive meaning and the degree of realness. The results of the study show that in term of the interactive meaning, the represented participant mostly look directly into the viewers which create a demanding gaze, it can be said that the producer of the PSA for Covid-19 in Indonesia intended to create some sort of persuasion for the viewers as the interactive participants to take some actions or to do something. Additionally, the Public Service Announcement also made in a way that encourage viewers to relate themselves with the represented participant and making both the viewers and the represented participant hold the same level of power. In terms of the degree of realness, it is also revealed that the PSA tends to give high value of realness or modality.